Policy to Improve the Quality of Education in Islamic Boarding Schools - Isrok, Isrok; Hakim, Dian Mohammad; Afifulloh, Moh. (Electronic Journal of Education, Social Economics and Technology, 2025)
This research aims to describe the implementation strategy of the quality improvement policy, the obstacles to implementing the quality improvement policy, and the solution to overcome the obstacles to implementing the quality improvement policy in MTs. Al Akhyariyah Panjalinan. The method of this research is to use a descriptive qualitative approach. The study results show the following: Implementation strategy for quality improvement policies at MTs. Al Akhyariyah Panjalinan has been running for its establishment. This can be seen from several indicators, including the standards and policy objectives that have been achieved, the resources that support it, communication between the principal and teachers, employees, and students runs smoothly, inter organizations and inauguration activities are running well, the characteristics of implementing supportive agents, as well as social, economic, and political conditions that are conducive and support the implementation strategy of quality improvement policies. The obstacles that arise in implementing quality improvement policies are low student understanding of the importance of education, inadequate number of educators, inadequate learning infrastructure, and the economic condition of students' parents classified as middle to lower economic levels. Solutions to overcome obstacles in the implementation of quality improvement policies are providing an approach so that students want to continue their education to the next level, finding substitute teachers according to the subject, procurement of infrastructure facilities through BOS funds, providing the Smart Indonesia Program (PIP) for underprivileged students.